Concomitant selective adsorption and covalent immobilization of a His-tagged protein switch with silica-based metal chelate-epoxy bifunctional adsorbents. (December 2020) - You, Chen-Xin; Huang, Po-Han; Lin, Sung-Chyr
Highlights: Silica-based metal chelate-epoxy bifunctional adsorbents were prepared. Selective adsorption by the bifunctional adsorbents were investigated. Kinetics of covalent immobilization by the adsorbent were elucidated. Enzyme immobilized on the bifunctional adsorbent exhibited superior stability. Graphical abstract: Abstract: A series of silica-based bifunctional adsorbents containing both metal-chelating groups and epoxy groups for the concomitant purification and immobilization of His-tagged protein switch RG13, a potential bioreceptor for developing maltose biosensors, were prepared by controlling the ratio of iminodiacetic acid-conjugated silane (GLYMO-IDA) and silane (GLYMO) used for surface modification. The bifunctional adsorbent prepared with a [GLYMO-IDA]/[GLYMO] ratio of 0.2, containing a [metal chelating group]/[epoxy group] ratio of 1.42, was shown to exhibit a metal chelating capacity of 88.42 ± 15.91 μ mole Cu 2+ /g, a protein adsorption capacity of 1.81 ± 0.19 mg/g and a superior selectivity over the other bifunctional adsorbents. Results of kinetic studies showed that selective adsorption and covalent bond formation at 4 °C were achieved in 1 h and 15 h, respectively, which allowed the sequential adsorption and covalent immobilization of protein switch RG13. A protein immobilization yield of 94.6 % and a global activity yield of 63.4 % were obtained, giving an immobilized protein switch RG13 with an enzymatic activity of 4.57 ± 0.19 U/g, under optimal conditions at pH 8.0 and 40 °C. In the repeated-batch operation, the bifunctional adsorbent-immobilized RG13 retained 91 % of the original activity after 20 cycles, 39 % higher than the counterpart prepared with monofunctional metal chelate adsorbent mediated solely by coordinate linkages.